Perceived diversity and skill diversity to utilise demographic diversity: evidence from the factors of employee attitudes in a large Japanese company - Azusa Kadomura; Akiyuki Sekiguchi; Takumi Kato (Humanities & Social Sciences Communications)
Abstract In response to the demands of the times, companies proactively introduce diversity into their organisations and strengthen internal and employee branding. However, diversity is a double-edged sword that can promote or hinder organisational performance. Although strengthening the environment in which diversity can be utilised is a priority to obtain the positive effects of diversity, limited knowledge has been accumulated on this topic. This is because diversity has been examined only in terms of demographic diversity, disregarding the combination of diversity with other aspects. Consequently, this study classified diversity into three categories—demographic, perception, and skill diversity—and analysed their moderating effects. This study’s structural equation modelling results, from an online survey of 3000 full-time employees of Panasonic Connect Co., Ltd. in Japan, found a significant positive effect of demographic diversity × perceived diversity on meaningfulness of work. Additionally, a positive impact of demographic diversity × skill diversity was identified on organisational identification and meaningfulness of work. However, demographic diversity × skill diversity may increase the risk of burnout, given that it may intensify competition among employees. These results provide new knowledge regarding specific organisational strategies to utilise diversity, which has been a concern owing to its negative side effects.